Insights into the Electron Transfer Kinetics, Capacitance and Resistance Effects of Implantable Electrodes Using Fourier Transform AC Voltammetry on Platinum. Issue 12 (1st January 2019) - Harris, Alexander R.; Newbold, Carrie; Cowan, Robert; Wallace, Gordon G.
Abstract : The charge transfer mechanism at the electrode-solution interface was assessed by Fourier transform AC voltammetry (FTACV). The faradaic reactions that occur within the safe potential window on platinum had slow electron transfer kinetics. The charge transfer mechanisms during short chronopotentiometric stimulation of cells, is most likely dominated by capacitance. Impedance was modelled with a single time constant. FTACV was fit with a 2-component equivalent circuit comprising a series capacitor and resistor. Capacitance and resistance varied with electrode potential, area, topography, surface functionality and solution composition. Capacitance correlated with charge storage capacity measured by voltammetry. Increased capacitance reduced the change in potential during chronopotentiometry. Increased resistance resulted in uncompensated resistance, and a larger change in potential during chronopotentiometry. Uncompensated resistance in tissue may lead to the measured potential of an electrode being considerably higher than its true potential, leading to a conservative estimate of the safe operating potential window. An impedance test is used to assess electrode performance in vivo. The impedance test is a function of capacitance, faradaic charge and resistance. Impedance test results allow electrode comparison, indicating changes in electrode-tissue interface, electrode failure and power usage, however use of Ohm's law to calculate an impedance value is not valid.